2020
DOI: 10.1088/2053-1591/ab71ca
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of factors that affect thermal conductivity in epoxy composites with hybrid carbon nanotube and graphene nano platelet

Abstract: Carbon Nanotubes (CNTs) and Graphene Nano Platelets (GNPs) had been used to enhance the thermal conductivity of the epoxy composites and show a synergistic effect. Complex service conditions also put forward the requirements for the structural design of the composites to get better performance. Researches should be done to further understand the mechanism of enhancement in composites and find ways to assist the design and optimization of the structure. In this research, epoxy composites with CNTs, GNPs and hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The presence of 2 wt% of MWCNT, appears to distort the preferential orientation of the GNP at 1 wt%, and hence in composite D, a decrease in thermal conductivity is observed in the in‐plane direction. From reported studies, [ 36 ] it is observed that the MWCNT get stuck to the surface of GNP. This does not seem to be true in all cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of 2 wt% of MWCNT, appears to distort the preferential orientation of the GNP at 1 wt%, and hence in composite D, a decrease in thermal conductivity is observed in the in‐plane direction. From reported studies, [ 36 ] it is observed that the MWCNT get stuck to the surface of GNP. This does not seem to be true in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported in literature, [ 28,36,37 ] that in addition to the aspect ratio of GNP, the orientation of the carbon fillers is strongly dependent on the ratio of the fillers used. Generally, it is observed that if the fillers establish contact with the fiber direction, highest thermal conductivity is observed, since the fillers preferentially orient along the direction of glass fibers for better phonon transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, hybridization of 1D with 2D nanomaterial can also form an efficient 3D thermal conductive network that can supply fast phonon channel transport due to the extended contact area formed through the line contact. Figure 22 shows that the 3D network was formed when hybridizing GNPs and CNT reported by Wang e al 93 . The large surface of 2D fillers was observed gives enough adsorption space for 1D fillers like CNT to disperse in the polymer matrix that prevented the GNPs from agglomerate and built the bridges between them.The 2D filler is known to have a very high rigidity that can hinder it from bending, especially at high volume fraction 49 .…”
Section: Polymer Composites As New Die‐attach Materialsmentioning
confidence: 76%
“…Figure 22 shows that the 3D network was formed when hybridizing GNPs and CNT reported by Wang e al. 93 The large surface of 2D fillers was observed gives enough adsorption space for 1D fillers like CNT to disperse in the polymer matrix that prevented the GNPs from agglomerate and built the bridges between them.The 2D filler is known to have a very high rigidity that can hinder it from bending, especially at high volume fraction. 49 Therefore, the AR of 2D fillers is maintained and can provide more contact area with 1D fillers, which reduces the TBR and ITR, thus exhibiting high TC.…”
Section: Hybrid Polymer Compositementioning
confidence: 99%
See 1 more Smart Citation